Innovations and Structural Problems of Industry: Comparative Analysis of Azerbaijan’s Indicators with Turkish Republics - Gulshen Yuzbashiyeva; Samira Abasova; Israfil Yuzbashiyev (Challenges and Issues of Modern Science)
Azerbaijan's economy has a tendency for the growth of industry (processing), to strengthen the role of industry on an innovative basis, creating the foundations of sustainability and stability in conditions of depletion of natural resources and deterioration of the environmental condition. Therefore, an idea is being formed about a new quality of economic growth, which assumes a preferential increase in production due to intensive factors of growth and development; orientation towards final production that satisfies the consumer needs of the population; a combination of economic growth rates with the structural restructuring of production, as it ensures the necessary quality of economic growth and development. If the structure of the economy meets the requirements of modern economic growth and development, then this structure provides a new quality of economic growth and vice versa. It is important to know at the expense of what resources structural changes will occur, what investments will be needed for this, and how much the existing structure will contribute to the flow of investment. A qualitatively new structural policy is advisable, based on an analysis of the changes that have been observed in recent years of economic development. It is these quantitative and qualitative changes that increase the relevance of management influence on the economic structure, which requires an assessment of the ongoing structural changes, that is, the current situation and the realities of the investment process. The main problems of industrial growth are 1) inefficient sectoral and technological structure of the industry (high-tech production - 2-3% of output, although in developed countries it is 15-17%); 2) low labor productivity; 3) high material intensity, energy intensity, import dependence, low level of use of public investment, low level of coordination, modern equipment is purchased for the production of non-innovative products.